Mental Health Concerns of Students on the Autism Spectrum. Issue 156 (7th December 2016) - Brown, Jane Thierfeld; Meeks, Lisa; Rigler, Michelle
Abstract : This chapter introduces the reader to the autism spectrum and discusses the characteristics, traits, common concerns, and potential supports for this population. The chapter also provides some recommendations for proactive and collaborative support efforts for students with both an autism spectrum disorder and mental health issues.